Responsibilities of Da'wah Institutions in Human Resource Development - Mustarim Ramadhan; Cecep Castrawijaya (Advances In Social Humanities Research, 2023)
Da'wah institutions are social institutions that are active in the field of Islamic da'wah, both local and regional or national level institutions. HR (Human Resources) is one of the most important factors and cannot even be separated from an institution, organization, institution or company. Indonesia itself has regulations governing human resource development. That is, workforce is everyone who does work to produce goods and/or services both to meet their own needs and those of the community as stated in article 1 point 2 of Law Number 13 of 2023 concerning Manpower. To achieve institutional goals, increase productivity, and maintain a company's competitive advantage, human resources are very important. Human resources are a very important resource for any institution or organization because they are the ones who really carry out all the functions of the institution. The development of an institution depends on its Human Resources. HR development is one of the efforts made by the institution to improve the performance of its members/employees. Institutions certainly have their own methods in developing the quality of human resources. Training human resources is not necessarily a matter of providing material, practice, trials and more. However, organizers must know what exactly is the definition of this program, what are its objectives, what are the benefits, and other things such as Zakat institutions, educational institutions, and Hajj and Umrah travel agency institutions.